2007
DOI: 10.1136/hrt.2008.142083
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in myocardial stiffness in elite athletes assessed by a new Doppler index

Abstract: Intense training reduces myocardial stiffness despite the development of LVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Although, the number of studied cases are too small too draw a statistically significant conclusion, this difference in cardiac stiffness might be a confirmation on age dependency of left ventricular function, 53 particularly corroborating that the heart gets stiffer and less compliant with age. 20,29,39 Additionally, we found that the slope of the viscous damping functions follow similar patterns for each individual age group (Fig. 8).…”
Section: Effect Of Agingsupporting
confidence: 52%
“…Although, the number of studied cases are too small too draw a statistically significant conclusion, this difference in cardiac stiffness might be a confirmation on age dependency of left ventricular function, 53 particularly corroborating that the heart gets stiffer and less compliant with age. 20,29,39 Additionally, we found that the slope of the viscous damping functions follow similar patterns for each individual age group (Fig. 8).…”
Section: Effect Of Agingsupporting
confidence: 52%
“…Stroke volume was calculated by using the aortic valve pulsed wave Doppler method whereby the velocity time integral of aortic annular flow was obtained by tracing the pulsed Doppler profile and multiplied by the area of the aortic annulus as previously described (30). Pre-load recruitable stroke work index, peak power index, single beat estimated end-systolic elastance, arterial elastance (31-33), chamber stiffness (34), pressure volume ratio (35), and longitudinal reserve indexes (36) were calculated:…”
Section: -Dimensional and Tissue Doppler Echocardiographymentioning
confidence: 99%
“…The mean values of Ea velocities were used to calculate the E/Ea ratio. Myocardial diastolic stiffness index was calculated using the equation of (Stiffness index = [(E/Ea)/LVIDd]) [14].…”
Section: Methodsmentioning
confidence: 99%